2011
DOI: 10.1016/j.stem.2011.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Cancer-Stem-Cell-Associated Wnt Target Genes Predicts Poor Prognosis in Colorectal Cancer Patients

Abstract: Gene signatures derived from cancer stem cells (CSCs) predict tumor recurrence for many forms of cancer. Here, we derived a gene signature for colorectal CSCs defined by high Wnt signaling activity, which in agreement with previous observations predicts poor prognosis. Surprisingly, however, we found that elevated expression of Wnt targets was actually associated with good prognosis, while patient tumors with low expression of Wnt target genes segregated with immature stem cell signatures. We discovered that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
178
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(194 citation statements)
references
References 27 publications
15
178
1
Order By: Relevance
“…These associations make sense also in light of previous studies, since MSI tumors are often associated with an inflammatory immune infiltrate and a mucinous phenotype, 3 and poor prognosis CRC (CCS3-serrated) has previously been shown to display a stem cell-like gene expression signature. 4,5 Thus, we found that 2 of the De Sousa E Melo et al subtypes were simply subdivided to generate a total of four subsets in the Sadanandam et al study.…”
Section: Resultsmentioning
confidence: 86%
“…These associations make sense also in light of previous studies, since MSI tumors are often associated with an inflammatory immune infiltrate and a mucinous phenotype, 3 and poor prognosis CRC (CCS3-serrated) has previously been shown to display a stem cell-like gene expression signature. 4,5 Thus, we found that 2 of the De Sousa E Melo et al subtypes were simply subdivided to generate a total of four subsets in the Sadanandam et al study.…”
Section: Resultsmentioning
confidence: 86%
“…Using unsupervised classification of transcription data, independent groups have reported 3 to 6 molecular subgroups within colorectal cancer (2,4,7). Recent subtype concordance analysis by the Colorectal Cancer Subtyping Consortium (CRCSC) has yielded a consensus of 4 transcriptionally driven colorectal cancer molecular subgroups [Consensus Molecular Subtype (CMS 1-4)] with the following distinguishing features: CMS1, microsatellite instable (MI)/immune [frequency (f) ¼ 14%); CMS2, canonical (f ¼ 37%); CMS3, metabolic (f ¼ 13%); and CMS4, mesenchymal (f ¼ 23%; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the studies highlighted above (2,4,7) suggested that the identification of the CMS4 subtype was evidence of epithelial tumor cells undergoing changes associated with an extensive epithelial-mesenchymal transition (EMT), resulting in increased invasion and the acquisition of stem cell properties that are necessary for the establishment of metastases (10). Although the findings of these studies were independently validated, the cellsof-origin of individual transcriptional subtypes were not defined.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the genes and encoded proteins that participate in the maintenance of stemness and in the EMT 4 in colon cancer cells, which contain a population of colon cancer progenitor cells (1)(2)(3). Indeed, it is important to identify the regulatory mechanisms and signaling pathways involved in colon cancer cells to develop novel reagents that reverse the mesenchymal phenotype to the epithelial phenotype (4).…”
mentioning
confidence: 99%
“…Indeed, it is important to identify the regulatory mechanisms and signaling pathways involved in colon cancer cells to develop novel reagents that reverse the mesenchymal phenotype to the epithelial phenotype (4).…”
mentioning
confidence: 99%